The integration processes of the distributional patterns in the Mexican Transition Zone: Phyletic, paleogeographic and ecological factors of a case study - Halffter, Gonzalo; Zunino, Mario; Moctezuma, Victor; Sánchez-Huerta, José L. (Zootaxa, 2019)
In this study, we take the Onthophagus chevrolati species group, likely a monophyletic species group as an example to analyze the processes that led to the biogeographic integration of the Holarctic fauna in the mountains of the Mexican Transition Zone to test our biogeographic hypotheses. We propose a change from the status of subspecies to species for O. oaxacanus Zunino & Halffter, 1988 new status; O. howdeni Zunino & Halffter, 1988 new status; O. jaliscensis Zunino & Halffter, 1988 new status; O. longecarinatus Zunino & Halffter, 1988 new status; O. omiltemius Bates, 1889 revised status; and O. retusus Harold, 1869 revised status. Consequently, the O. chevrolati group of species is currently made up of 47 species belonging to four species lines: O. vespertilio, O. hippopotamus, O. cyanellus and O. chevrolati. The diversification of the Onthophagus chevrolati species group in this region resulted from three hypothetical stages of evolution. In the first, the penetration and expansion of the ancestor of the O. chevrolati species group occurred before the Miocene and the Trans-Mexican Volcanic Belt arose. During the second stage, the O. hippopotamus species line expanded and evolved, integrating with the paleogeographic changes and the formation of the Trans-Mexican Volcanic Belt, as a consequence of volcanism during the Miocene-Pliocene. In the third and most recent stage, the O. chevrolati species line used the existing mountain systems and interglacial climate fluctuations of the Pleistocene to expand and diversify. Thus, the mountains of the Mexican Transition Zone are not simply periglacial refugia. The entomofauna of Holarctic origin present in the region evolved while the Earth’s geological processes were underway.